Recent Progress in the Application of Exosome Analysis in Ovarian Cancer Management - Keyvani, Vahideh; Ghale-Noie, Zari N.; Mollazadeh, Samaneh; Mahmoudian, Reihaneh Alsadat; Ghorbani, Elnaz; Naderi, Hamid; Khazaei, Majid; Hassanian, Seyed Mahdi; Ferns, Gordon A.; Avan, Amir; Anvari, Kazem (Current Cancer Drug Targets, 2024)
Exosomes are very small (nano-sized) vesicles participating in tumor development by involvement in intercellular communication mediated by transferring biocomponents. Exosomes appear to play vital roles in various cancer development, such as ovarian cancer, a common malignancy in women. Several hallmarks of ovarian cancer are reported to be affected by the exosomemediated cellular cross-talk, including modulating peritoneal dissemination and chemoresistance. Since the expression of some biomolecules, such as miRNAs and mRNA, is changed in ovarian cancer, these exo-biomolecules can be applied as prognostic, diagnostic, and therapeutic biomarkers. Also, the selective loading of specific chemotherapeutic agents into exosomes highlights these biocarries as potential delivery devices. Exosomes could be artificially provided and engineered to better target the site of interest in ovarian cancer. In the present review, we summarize the notable achievement of exosome application in ovarian cancer management to gain applicable transitional insight against this cancer.
Keywords: delivery vehicles